Evaluating an ai-supported experiential learning intervention: a quasi-experimental study of the joyful saturday model for student engagement and holistic development - Bhargav Rajyagor; Paresh Vora (International Journal of Behavioral Sciences, 2026)
Student disengagement, declining academic motivation, and passive classroom participation remain major challenges in modern higher education systems. Traditional lecture-based teaching methods often fail to accommodate diverse learning styles and do not sufficiently promote active participation or collaborative learning. To address these challenges, the present study evaluates the effectiveness of Joyful Saturday, a structured experiential learning initiative designed to improve student engagement, motivation, and holistic development through interactive academic activities supported by data-driven evaluation methods. A quasi-experimental pretest–posttest control group design was implemented over a twelve- week period involving 642 students from both school and college levels. The intervention included structured weekly experiential sessions that incorporated innovation workshops, collaborative problem-solving tasks, reflective learning exercises, and peer-learning activities. Key outcome variables—including student engagement, academic motivation, attendance, psychological well-being, and collaborative skills—were measured using validated psychometric instruments with strong reliability indicators. Statistical analysis was conducted using paired sample t-tests, analysis of covariance (ANCOVA), and multiple regression analysis to examine the effectiveness and robustness of the intervention. The results demonstrate statistically significant improvements across all measured variables (p < .001), with effect sizes ranging from moderate to high (d = 0.48–0.92). Engagement scores increased substantially, accompanied by notable improvements in motivation, attendance rates, and student well-being. Regression analysis further revealed that collaborative participation emerged as the strongest predictor of positive academic outcomes (R² = 0.61), highlighting the importance of peer interaction in experiential learning environments. Overall, the findings indicate that structured experiential learning initiatives supported by analytical evaluation can significantly enhance student engagement and academic development. The Joyful Saturday model offers a scalable and practical framework for integrating experiential learning with data-driven educational decision-making, providing valuable implications for institutional innovation and policy development in contemporary higher education systems.
Keywords: Active learning; Collaborative learning; artificial intelligence in education; educational innovation; experiential learning; learning analytics; student engagement